2020
DOI: 10.1080/11038128.2020.1750692
|View full text |Cite
|
Sign up to set email alerts
|

Womenʼs experiences of being in the sick leave process

Abstract: Background: Being on sick leave is a risky situation, with loss of meaningful activities, exclusion from the labour market and losing the worker role. Although the benefits of the person's active involvement in the sick leave process have been emphasized, an increase in sickness absence and longer sick leave periods is still seen, especially among women. Further studies are needed to more deeply understand the person's own view of the situation. Aims/Objectives: To explore the experiences of being on sick leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Our participants viewed their identities as challenged or under threat while on sick leave owing to chronic pain. This feeling is consistent with previous findings on the sick leave process due to other health conditions, expressed as being reduced as a person and not recognising oneself 15 or experiencing a changed self-perception. 18 Our participants depicted a strong connection between identity and work.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our participants viewed their identities as challenged or under threat while on sick leave owing to chronic pain. This feeling is consistent with previous findings on the sick leave process due to other health conditions, expressed as being reduced as a person and not recognising oneself 15 or experiencing a changed self-perception. 18 Our participants depicted a strong connection between identity and work.…”
Section: Discussionsupporting
confidence: 93%
“…However, our participants reported feeling subservient and helpless, with their lives dependent on the goodwill of institutional gatekeepers. Previous research on sick leave has observed similar experiences, that is, instead of a partnership, the rules and regulations make the stakeholders become counterparts, leaving little flexibility for the person 15. But being on sick leave due to chronic pain was also interpreted as different from other health issues, mainly because of its invisibility and the lack of objective assessment of pain symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Too much was left to the individual to decide, with the risk of not being able to make a decision, or choosing and doing too much. A better understanding of the different factors that contribute to the potential for increased return to work could be warranted [ 27 , 28 ]. Engaged professionals need to provide just the right information and planning related to the individual situation, and this could also be discussed in relation to ethical considerations [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PEOP Model provided a framework for investigations of populations that need a stronger voice in occupational therapy research. For example, articles highlighted international perspectives from Iran (Akbarfahimi et al, 2020), Sweden (Andersson & Mårtensson, 2021;Johansson et al, 2021), Thailand (Chaimaha & Chinchai, 2016;Chaimaha et al, 2017;Chupradit et al, 2021), Australia/New Zealand (Maher et al, 2018;Wilson et al, 2013), Philippines (Caday et al, 2022), China (Wan et al, 2022, and the United Kingdom (Cordingley & Ryan, 2009;Maher et al, 2018). Black, Indigenous, and People of Color (BIPOC) perspectives were obtained in studies of underrepresented college students (Clifton & Taff, 2021;Shraga-Roitman et al, 2022), aging Puerto Ricans (Orellano-Colón et al, 2014, African American fathers (Pizur-Barnekow et al, Digital books (Bibb et al, 2012) Assistive devices for positioning and sleep (Ho & Siu, 2018) Design of equipment and devices (Naweed et al, 2020(Naweed et al, , 2022 Remote monitoring systems (Rich et al, 2020) Accessibility of online reservation system (Stasell & Bathje, 2021) Media distractions in the sleep environment (Yang & Smallfield, 2020) 2017), and African Americans with disabilities (Schulz et al, 2022).…”
Section: Group Of Individuals With Common Characteristics More Than O...mentioning
confidence: 99%